Sosialisasi Teknik Menyikat Gigi dan Pemeriksaan Gigi dan Mulut Pada Siswa-Siswi SDN 106813 Desa Amplas Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Waty, Syahdiana; Herlinawati, Herlinawati; Nurhamidah, Nurhamidah; Siregar, Rawati; Aritonang, Netty Jojor; Aritonang, Intan; Sondang, Sondang; Syafriani, Irma; Sari, Berliana; Dhewi, Shiska Buwana (Universitas Islam Negeri Sumatera Utara, 2024)
Dental and oral health is a very important part of general health. Damage to teeth can affect human quality of life. Therefore, it is very important to maintain the oral cavity and teeth so that they remain healthy. The most important preventive measure so that teeth don't get damaged quickly is to maintain proper oral and dental hygiene every day, namely by brushing your teeth. . Brushing your teeth regularly and correctly is the main method for removing plaque and controlling diseases caused by plaque, such as caries and periodontitis. Counseling is an effort that can be made to change children's actions in maintaining dental and oral health so that optimal levels of dental and oral health are achieved. Counseling is carried out using the lecture method and using pantomime. This community service activity was carried out in the form of socializing tooth brushing techniques and carrying out dental and oral examinations for 76 students of SDN 106813 in Amplas Village, Percut Sei Tuan District, Deli Serdang Regency. Community service activities have been carried out, with the results obtained that the def-t number is 322 with an average def-t of 4.24. This condition is in the high category and some of the students' permanent teeth already have caries.